Pediatric Sepsis: Clinical Considerations - Balázs, G.; Szima, S.; Elek, N.; Dahlem, P. (Journal of Child Science, 2017)
Sepsis remains one of the leading causes of childhood mortality today, although survival has substantially improved, thanks to an ever deeper and more thorough understanding of sepsis pathophysiology, developments in vaccination and intensive therapy, and goal-directed therapeutic approaches. The key to successful therapy is early recognition and antibiotic treatment, as well as supportive therapy aimed at correcting circulatory, respiratory, and metabolic derangements as soon as possible. Diagnosis and management of childhood sepsis mainly evolves along the path of studies conducted in adult patients; however, their applicability is limited due to a variability of cardiovascular and immune responses in each age group. In addition to childhood characteristics of hemodynamic responses in sepsis, this review looks at major areas of pediatric sepsis therapy, with the intention of providing bedside clinicians with pointers useful in their day-to-day work.
Keywords: sepsis; septic shock; children; pediatric; infection; review